2017
DOI: 10.5430/jms.v8n3p67
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Attitudes towards Ecotourism Benefits on Destination Loyalty

Abstract: This study aims to examine the impact of attitudes towards ecotourism benefits (using the variables of economic development, social development, cultural preservation, community capacity building, and environmental protection) on destination loyalty of Wadi-Rum located in Jordan. A total of 297 questionnaire containing 29 items was used to collect information from the local residents of Wadi-Rum. Simple regression, T-test, and ANOVA analyses were conducted to test the research hypotheses. Results of the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(14 reference statements)
0
4
0
1
Order By: Relevance
“…The first cluster presented concerned the impact of attitudes towards the benefits of ecotourism on loyalty to destinations presented by Bazazo et al (2017). The authors used the variables of economic development, social development, cultural preservation, community capacity building and environmental protection on allegiance to the Wadi Rum destination in Jordan.…”
Section: Discussionmentioning
confidence: 99%
“…The first cluster presented concerned the impact of attitudes towards the benefits of ecotourism on loyalty to destinations presented by Bazazo et al (2017). The authors used the variables of economic development, social development, cultural preservation, community capacity building and environmental protection on allegiance to the Wadi Rum destination in Jordan.…”
Section: Discussionmentioning
confidence: 99%
“…De acordo com Souza (2007), uma das contribuições possíveis de uma rede de monitoramento baseada em indicadores está na produção de "informações confiáveis sobre o estado e a evolução dos fatores ambientais, bem como de seus graus de resiliência (ecológica e cultural) frente a possíveis alterações de seus componentes". Para a realização das atividades de ecoturismo é preciso implementar planos de gestão com vistas a garantir profissionalismo, treinamento, melhoria profissional da organização dos atrativos para os operadores e adequada regulamentação dos fluxos turísticos (Bazazo et al, 2017). O ordenamento do ecoturismo no Parque Nacional de Anavilhanas, apresentado por Vidal et al (2017), tem se mostrado um exemplo, proporcionando melhor interação dos visitantes com os cetáceos, além de possibilitar melhor monitoramento da área pelos funcionários.…”
Section: Discussionunclassified
“…Attitudes towards tourism is positively associated with DL (Bazazo et al, 2017). On the contrary, preceding research showed that individuals (e.g., tourists and residents) may show a negative attitude towards a place/location and be loyal to it through their willingness to revisit, recommend it, and/or by spreading positive word of mouth (PWOM) (Ribeiro et al, 2018;Wang et al , 2017).…”
Section: Attitude Towards Tourism and DLmentioning
confidence: 94%